Stature Estimation Based on Fingers Anthropometry in Iranian Population - Sina Mojaverrostami; Tahmineh Mokhtari; Mehrnoush Malekzadeh; Leila Noori; Shokoofeh Kazemzadeh; Sahar Ijaz; Ibrahim Mohammed; Gholamreza Hassanzadeh (Negah Institute for Scientific Communication, 2019)
Introduction: The stature is one of the determinant factors to identify a person. We investigated the possibility of predicting stature based on Fingers Length in Iranians. Methods: We studied 195 healthy Iranian students (97 females and 98 males) of Tehran University of Medical Sciences. The correlation between stature and fingers anthropometric measurements was investigated and equations for stature prediction were demonstrated by linear regression analysis.  Results: According to the obtained results, males had higher mean values in each anthropometric measurement, compared to females. Third Finger Length (3rd FL) indicated higher correlation coefficients with stature in both genders. Regression analysis suggested a lower Standard Error of Estimate (SEE) in females (±4.91-5.60 cm), than males (±5.87-6.74 cm). Conclusion: 3rd FL provides a better prediction of stature among the lengths of fingers in both genders.